Melmoth the Wanderer: uma proposta de tradução comentada - Fonseca, Juliana Gallo da (2019)
The present work aims to make the commented translation of the first volume of the work Melmoth the Wanderer, written in 1820 by the Irish Charles Robert Maturin. The book tells the story of John Melmoth, a student who discovers the existence of an ancestor who sold his soul to the devil. The first chapter here deals with the historical context in which Gothic Literature emerges and in which Melmoth the Wanderer is inserted. A brief summary of the author's life is also presented, as well as an expanded summary of the book, its narrative structure, and also the author's influences, as well as its reception among the public. The third chapter is about the translation process and the translation method itself, bringing the concepts of foreignness and domestication discussed mainly by Antoine Berman and Lawrence Venuti. Finally, the translation of selected excerpts is presented to demonstrate their challenges and the process of translation choices.